Análise das transações e estruturas de governança na cadeia produtiva do leite no Brasil: a França como referência - BANKUTI, Sandra Mara Schiavi (2007)
Since the 90 decade, Brazilian milk sector has suffered important changes, mainly due to macroeconomic, concurrential and consumption modifications in the country. Among those changes, it is been observed new transaction forms between rural producers and milk processing companies. Governance structures between those agents are still under construction, thus not being considered definitive. In some countries, such as France, it is possible to note high coordination level in the chain and consolidated governance structures. The present thesis has analyzed transactions and governance structures between milk producers and processing companies in the region of São Carlos /SP and in the western region of France. Theoretical fundaments of New Institutional Economics, Transaction Cost Economics and Industrial Organization are considered. To accomplish the work, it has been used secondary data, as well as field research in the two countries, with rural producers, milk processing companies representatives and key-agents. It has been identified bilateral governance in the region of São Carlos /SP, and trilateral governance in the West of France. Besides the predominance of informal contracts in both studied regions, it has been observed differences in terms of transaction characteristics and negotiation aspects. Such differences are due to distinctions of institutional and organizational environments, agents and coordination level. It has also been concluded that not only transaction attributes influence governance structures. The work remarks the role of trust, power in the relation and dependence between agents as relevant aspects to understand transactions and governance structures.